2022
DOI: 10.1186/s12877-022-02948-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynapenic abdominal obesity is associated with mild cognitive impairment in patients with cardiometabolic disease: a cross-sectional study

Abstract: Background Dementia is an important health issue for older people and requires early intervention in the mild cognitive impairment (MCI) stage to manage risk factors. Both dynapenia (DP) and abdominal obesity (AO) are associated with inflammation and oxidative stress, which may be involved in the pathogenesis of cognitive impairment. Therefore, in this cross-sectional study, we aimed to evaluate the association between MCI and dynapenic abdominal obesity (DAO), a combination of DP and AO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our novel finding that sedentary behavior is associated with an increase in odds for DAO is indeed an important finding as DAO has been shown to be related with multiple detrimental health outcomes, including, for example, cognitive impairment, falls, disability, and premature mortality [ 3 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our novel finding that sedentary behavior is associated with an increase in odds for DAO is indeed an important finding as DAO has been shown to be related with multiple detrimental health outcomes, including, for example, cognitive impairment, falls, disability, and premature mortality [ 3 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynapenic abdominal obesity (DAO) is defined as the coexistence of abdominal obesity and low muscle strength [1], and its prevalence has been reported to be high in the general population, particularly among older adults [2]. DAO is an emerging important risk concept as recent studies have shown that this condition is associated with a high risk for a myriad of adverse health outcomes including falls [3,4], cognitive impairment [5], worsening disability, and premature mortality [6]. Given this, it is particularly important to identify risk factors of DAO among the older population to Extended author information available on the last page of the article sedentary behavior can lead to central obesity, while sedentary behavior can potentially cause low muscle strength via absence of muscle contractile activity, and other physiological consequences on muscle metabolism [11].…”
Section: Introductionmentioning
confidence: 99%
“…This process generates DAO in the elderly, which is an important health problem, acting as a mediating factor that changes brain structure and function and affects cognitive function [ 5 , 14 ]. In this study, no significant relationship was found between abdominal circumference alone and MCI.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was demonstrated that DAO was related to MCI. However, sex differences were not confirmed because the analysis was not categorized by sex in that study [ 14 ]. Considering these characteristics in women, this study aims to determine the relationship between AO, DP, DAO, and MCI by considering differences in sex and analyzing how these relationships differ.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation